ASIMETRI INFORMASI SERTA IMPLIKASINYA TERHADAP PENGEMBALIAN INVESTASI SAHAM MANUFAKTUR DI INDONESIA - Jenny Sihombing; Lenita Waty; Hedry Purba (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2017)
This study aims to find out how the influence of disclosure on information asymmetry, the influence of information asymmetry on stock returns and the influence of disclosure on stock returns. The unit of analysis used is all existing manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study used descriptive verifikatif method with quantitative approach, partial least square statistical approach. The results of this study indicated that the increasing voluntary disclosure occured significantly influenced information asymmetry with a negative coefficients direction. Information asymmetry significantly influenced stock return with negative coefficient direction. Voluntary disclosure influenced stock return with positive coefficient direction. A Better supervision and motivations are needed so that the company's management disclose information exceed the requirements made by the regulator in order to generate benefit for investors as well as for the company. Keywords: voluntary disclosure, information asymmetry, investment, stock, manufacture.